KUASA ATAS RUANG PEMBEBASAN’: THE RESILIENCE OFWOMEN IN SASAK CULTURE - Wijayanti, Lucky (UI Scholars Hub, 2020)
The Sasak tribe on Lombok island - West Nusa Tenggara, have traditional values and are applied through the social structure of their communities in daily life. Some existing customary values place women in irreplaceable positions. Even so, the existence of financial needs makes them work abroad as laborers, which indirectly results in the occurrence of divorce and early marriage. This is a problem for Sasak women in terms of survival in the Sasak culture. An ethnographic approach derived from Malinowski, the opinion of Svasek, and the value system framework from Kluckhohn are used in this study. This research concludes that art activities are the livelihoods of Sasak women while at the same time functioning as a 'liberation room' for them to express themselves.